2017
DOI: 10.1093/omcr/omx076
|View full text |Cite
|
Sign up to set email alerts
|

Elevated homocysteine and N-methyl-d-aspartate-receptor antibodies as a cause of behavioural and cognitive decline in 22q11.2 deletion syndrome

Abstract: A 19-year-old male with 22q11.2 deletion syndrome presented with a 4-year history of cognitive decline and symptoms suggestive of atypical psychosis. Potential for elevated homocysteine and NMDA-receptor antibodies in the pathogenesis of his symptoms was investigated. He had elevated blood homocysteine level (18.7 μmol/l), low-normal vitamin B12 and folate levels and was positive for NMDA-receptor antibodies. Treatment with daily folinic acid (0.8 mg) and vitamin B12 (1 mg) led to dramatic improvement in his c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has subsequently been observed that during remission from psychosis, homocysteine levels drop [18]. Golimbet et al [19] identified a trend for a genetic association between the gene for CBS and schizophrenia in a study of 1,135 patients and 626 controls and Colafrancesco et al [20] published a case report on a teen with sudden onset psychosis and bilateral subluxation of the lens, diagnostic of CBS deficiency, later confirmed by molecular testing. The 22q deletion syndrome, which dramatically increases the risk of psychosis, can involve high levels of homocysteine [21].…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Increases ...mentioning
confidence: 99%
“…It has subsequently been observed that during remission from psychosis, homocysteine levels drop [18]. Golimbet et al [19] identified a trend for a genetic association between the gene for CBS and schizophrenia in a study of 1,135 patients and 626 controls and Colafrancesco et al [20] published a case report on a teen with sudden onset psychosis and bilateral subluxation of the lens, diagnostic of CBS deficiency, later confirmed by molecular testing. The 22q deletion syndrome, which dramatically increases the risk of psychosis, can involve high levels of homocysteine [21].…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Increases ...mentioning
confidence: 99%